Open innovation for property management in emergency and post-emergency pandemic regime - Massimo Lauria; Maria Azzalin (Agathón)
The paper introduces an ongoing research activity named BIMaid – Bim-basedforcovid19 Protocols. It is part of R&D program developed by BIG Srl – Academic spin-off of ‘Mediterranea’ of Reggio Calabria – aimed at innovative governance of real estate assets, that welcomes the challenge of managing buildings in an emergency and post-emergency regime from Covid-19. It proposes, through Smart BIM-based Protocols, methodological and process solutions to plan and manage the ‘new normal’, to guarantee social distancing, environmental sanitation, and adaptation of spaces. In general terms, it supports the ongoing transition towards a management policy that uses the tools of digital culture and interoperability to keep the main variables under control already in the decision-making phase.